Molecular Structure And Electronic Properties Of Eugenol And Its Analogues Using Dft - Mirella Fonda Maahury; Muhammad Abdulkadir Martoprawiro; Veliyana Londong Allo (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Eugenol is the active molecule naturally found in clove oil. The calculations have been done for the eugenol and its derivatives computationally. This computational calculation aims to obtain a stable structure and electronic properties of eugenol, methyl eugenol, and acetyl eugenol. The computational calculation used DFT for geometry optimization in the gas phase using B3LYP functional and 6-31G(d) as the basis set. The optimized structure of eugenol and its derivatives is not planar. The presence of methoxy replacing hydroxy increases the bond length and decreases the bond angle and the dihedral. The electronic properties such as atomic charge and density of HOMO-LUMO show the difference between the three molecules.